Pengaruh Kompensasi dan Stress Kerja Terhadap Kepuasan Kerja Serta Dampaknya Pada Kinerja Karyawan (Kasus PT. Pos Indonesia Cabang Bekasi Timur) - Yolanda Yolanda; Limah Salbawati (Fakultas Ekonomi Universitas Borobudur, 2020)
This study aims to determine the extent of the influence of compensation, job stress onemployee performance through job satisfaction at PT. Pos Indonesia (East Bekasi Branch). Thedata used in this study are primary data collected from respondents' answers based on thequestionnaire given, namely as many as 100 people. The data processing method uses the pathanalysis method with the help of SPSS version 22.0. Statistical testing used individual parametersignificance test (t test), simultaneous significance test (F test) and Sobel test. The results showedthat simultaneously the variables of compensation, job stress and job satisfaction have asignificant effect on employee performance. Partially it shows that analysis 1: the compensationvariable has a significant effect on employee performance, while analysis 2: the job stressvariable has a significant effect on employee performance and in analysis 3: the variable jobsatisfaction has a significant effect on employee performance.Keywords: Compensation, Job Stress, Job Satisfaction and Employee Performance